EFEKTIFITAS KEPEMIMPINAN YANG MEMBERDAYAKAN DALAM MENINGKATKAN PERTUMBUHAN GEREJA DI GEREJA JEMAAT KRISTEN INDONESIA MARANATHA UNGARAN - Gidion, Gidion (Shift Key : Jurnal Teologi dan Pelayanan, 2018)
Moses was a good leader, but he was the de facto who made Israel not move as fast as he wanted. He does not create a work culture that encourages strong movements by empowering his followers. He became the center of his community dynamics. As a result, the strength of the community is determined by its own strength, while the potential of others that God places around it, is neglected (Ex. 18: 17-18). But after Moses empowered, work was easier and more effective (Ex. 18: 21-23). Leaders who work hard on their own and do not do empowerment will slow the pace of developing organizations. The JKI Church of Marantha Ungaran has actually implemented an empowering leadership pattern, but it is not yet maximal. Therefore this study aims to find out how much empowering leadership effectiveness is in improving church growth in JKI Maranatha Uangaran